Formation and breakage of flocs using dual polymers - (:unkn) unknown (IWA PUBLISHING, 2006)
The effect of shear on the formation and break-up of flocs generated using cationic, anionic and non-ionic polymers, and dual combinations of these, has been investigated using conventional jar test procedure and by continuous optical monitoring. The breakage of flocs was followed at a high stirring speed, corresponding to average shear rate (G) of approximately 520 s(-1). Most of the breakage occurred within a few seconds of increasing the shear rate. After each breakage, the stirring rate was reduced to the original value of 50 rpm (G approximate to 23s(-1)) to allow the flocs to regrow. For cationic-anionic polymers case, the regrowth of flocs was fully reversible and the breakage factors were smallest indicating highest floc strength. In contrast, flocs formed using non-ionic polymer together with anionic or cationic did not produce as strong flocs. It is found that the sequence of polymer addition is not very significant for floc formation and reformation when the cationic-anionic dual system is used.
Keywords: dual polyelectrolytes; dual polymers; floc; floc breakage; floc strength; RE-FORMATION; FLOCCULATION; POLYELECTROLYTES